POLITICAL HISTORY OF THE PALWO 1400-1911 (1973)
The Palwo are a branch of the Lwo who settled on the northern part of Bunyoro-Kitara kingdom. Their history is essentially that of rivalry between two ethnic groups, the Lwo and the Bantu, vying for supremacy in the empire of Bunyoro-Kitara, Originating from the Sudan, the Lwo settled in the hitherto exclusively Bantu inhabited empire, overthrew the ruling dynasty, and set up a new one. While intermarrying with the majority Bantu population, the Lwo kings ensured that only sons born to them by their Lwo wives (full-blooded Lwo) succeeded them. It was an attempt by the Lwo to make the throne their exclusive preserve. When one of the Lwo kings found himself compelled by circumstances to bypass convention and chose one of his children born by a Bantu woman to succeed him, the Lwo protested. They attempted to undermine the authority of this Bantu king who had no other alternative than to wage a war to 'crush the rebellion'. Henceforth children bom by Bantu women ascended the throne. The period of the rule of the Lwo appeared to have ended. While taking refuge from the war which crushed their rebellion, a good number of the Lwo left Bunyoro-Kitara and established their hegemony in the neighbouring areas. But some of them later came back and with the coming of more Lwo from the Sudan and Northern Uganda, the Lwo population in Bunyoro-Kitara a century after their rebellion was back to nearly what it was before the war. But the memory of their clash with the Bantu king was not forgotten by the Lwo. To them, it was humiliating to be deprived of a throne which for centuries had been occupied by their own people. Taking the Northern extreme of present day Bunyoro district as their base, the Lwo directed their activities for the following two centuries towards regaining their lost privileged position in Bunyoro-Kitara empire. However, in spite of their success in undermining the authority of some Bantu kings and launching series of military attacks on them, in spite of their economic boom caused by the activities of foreign traders, and which the Lwo attempted to turn into military advantage, they never succeeded in winning back the throne of Bunyoro-Kitara. Kabalega, a Bantu king, permanently converted them into an insignificant minority in the empire.